Reality Therapy: Dapatkah Meningkatkan harga diri pada remaja ? - Sitti Rojiyah Nur Inyirah Puhi (Procedia : Studi Kasus dan Intervensi Psikologi, 2023)
Adolescence is a period that is strongly inﬂuenced by the peer environment and is very concerned about other people’s judgments about them. The existence of negative evaluations in adolescents causes adolescents to experience problems with self-esteem. They are often self-critical and have a hard time seeing the positive in themselves. This case study aims to determine the effect of reality therapy in increasing self-esteem in adolescents. The assessments given were interviews, observations, graphic tests, wartegg tests, and the Rosenberg self-esteem scale. The results of the intervention showed an increase in self-esteem in the subject which was marked by the ability of the subject to interpret the failures experienced, able to understand a problem from another point of view and able to manage thoughts in situations that are stressful or cause suffering. Keywords: Negative evaluation, reality therapy, self-esteem, teenagers   Abstrak Masa remaja adalah masa yang sangat dipengaruhi oleh lingkungan teman sebaya dan sangat memperhatikan penilaian orang lain terhadap mereka. Adanya evaluasi negatif pada remaja menyebabkan remaja mengalami masalah pada harga diri. Mereka sering mengkritik diri sendiri dan kesulitan melihat hal positif dalam dirinya. Studi kasus ini bertujuan untuk mengetahui pengaruh terapi realitas dalam meningkatkan harga diri pada remaja. Metode asesmen yang digunakan adalah wawancara, observasi, tes grafis, tes wartegg, dan skala harga diri Rosenberg. Hasil intervensi menunjukkan adanya peningkatan harga diri subjek yang ditandai dengan kemampuan subjek menginterpretasikan kegagalan yang dialami, mampu memahami suatu masalah dari sudut pandang lain dan mampu mengelola pikiran dalam situasi yang penuh tekanan atau menyebabkan penderitaan. Kata kunci: Penilaian negatif, terapi realitas, harga diri, remaja